Enzymatic depolymerization of polyethylene using a small laccase and its potential for bio-upcycling - Son, Hyeoncheol Francis; Hwang, Sungmin; Kim, Yujin; Ahn, Jung Ho; Ko, Ja Kyong; Gong, Gyeongtaek; Um, Youngsoon; Park, Jong Hyuk; Park, Hyun June; Lee, Sun-Mi (Elsevier BV, 2025)
Polyethylene (PE) plastics present significant environmental challenges due to their recalcitrant nature and widespread usage. This study explores the biological degradation of PE using a novel enzyme, small laccase from Amycolatopsis sp. ATCC 39116 (ASLAC). Among four selected laccases, ASLAC demonstrated the highest biomass production using PE as a carbon source when expressed by Yarrowia lipolytica. Surface analysis of PE films treated with purified ASLAC, using scanning electron microscopy (SEM) and atomic force microscopy (AFM), revealed substantial degradation of the material. The degradation products were successfully utilized by Y. lipolytica, underscoring its potential for converting PE into bioenergy. Structural analysis and molecular docking simulations revealed that the substrate binding site of ASLAC, characterized by a hydrophobic planner configuration, is highly optimized for binding and cleaving PE polymers. This unique structure distinguishes it from other laccases with narrower or obstructed binding sites. Phylogenetic analysis of 311 small laccase sequences classified ASLAC into the Type-Ia subgroup, which exhibited superior potential for PE degradation. This study establishes ASLAC as a promising biocatalyst for sustainable PE management, providing a foundation for future applications in bioremediation and polymer upcycling.